Mary Pope Osborne's Magic Tree House : The Knight at Dawn - Book 2 2, The knight at dawn - Laird, Jenny, 1969-; Matthews, Kelly (Comic book artist); Matthews, Nichole; Osborne, Mary Pope. (New York : Random House, 2021)
"Retells, in graphic novel form, the tale of eight-year-old Jack and his younger sister Annie, who are whisked back in the magic treehouse to the time of knights and castles"--
Keywords: Time travel -- Comic books, strips, etc; Knights and knighthood -- Comic books, strips, etc; Middle Ages -- Comic books, strips, etc; Tree houses -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Time travel -- Fiction; Knights and knighthood -- Fiction; Middle Ages -- Fiction; Tree houses -- Fiction; Magic -- Fiction; Cartoons and comics; Fantasy comics; Graphic novels